2021
DOI: 10.3390/s21124111
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Radiation Effects on Fiber Optic Sensors

Abstract: Optical fiber sensors (OFS) are a potential candidate for monitoring physical parameters in nuclear environments. However, under an irradiation field the optical response of the OFS is modified via three primary mechanisms: (i) radiation-induced attenuation (RIA), (ii) radiation-induced emission (RIE), and (iii) radiation-induced compaction (RIC). For resonance-based sensors, RIC plays a significant role in modifying their performance characteristics. In this paper, we numerically investigate independently the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The optical fibers play a very important role in the telecommunication and sensing fields being used in diverse applications. In the recent years researchers have demonstrated that the gamma-rays and/or X/UV radiation changed the optical properties and have induced radiation attenuation in the optical fibers [12,13,14] . The effects of high frequency radiation interacting with the detecting optical fibers were analyzed by recording transmitted spectra before and after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The optical fibers play a very important role in the telecommunication and sensing fields being used in diverse applications. In the recent years researchers have demonstrated that the gamma-rays and/or X/UV radiation changed the optical properties and have induced radiation attenuation in the optical fibers [12,13,14] . The effects of high frequency radiation interacting with the detecting optical fibers were analyzed by recording transmitted spectra before and after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, radiation-induced compaction has been calculated using power law [3] and empirical equation [1]. Then, Lorentz-Lorenz relationship, point dipole theory, sensitivity factor, and a few empirical equations have been utilized to find out the change in RI and linear compaction from the volume compaction [3,9,44,[46][47][48]. An immediate question arises on whether these methods (Lorentz-Lorenz, point dipole theory) consider the combined RIC, RIA and dopant diffusion effects on the RI change or only consider the RIC effects on the RI change.…”
Section: Introductionmentioning
confidence: 99%